The Role of School Principals in Implementing Deep Learning at Elementary Schools in Panggul District, Trenggalek - Tinuk Lastriatun; Yepi Sedya Purwananti; M. Abdul Roziq Asrori; Dian Septi Nur Afifah (CV. Media Digital Publikasi Indonesia, 2025)
Twenty-first-century learning demands that elementary schools develop learning processes that are not merely oriented toward content mastery but also toward deep understanding and higher-order thinking skills. The deep learning approach is considered relevant because it emphasizes meaningful, reflective, and applicable learning. This study aims to analyze the role of school principals in implementing deep learning at elementary schools in Panggul District, Trenggalek Regency. A qualitative descriptive approach was employed, with data collected through in-depth interviews, classroom observation, and documentary analysis involving school principals and teachers. Data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing, with data validity assured through source and technique triangulation. Findings reveal that school principals serve as instructional leaders through planning, implementation, and academic supervision functions. Support was provided through the formulation of school policies, strengthening of learning planning, facilitation of teacher collaboration, and provision of professional support. However, academic supervision still tends to focus on administrative aspects and has not fully emphasized the quality of the classroom learning process. This study underscores the importance of strengthening instructional leadership and process-based academic supervision to ensure the sustainable implementation of deep learning at the elementary school level.